SINERGI KEBIJAKAN SEKOLAH DAN PARTISIPASI ORANG TUA DALAM MEWUJUDKAN PENDIDIKAN BERKUALITAS DI SD SWASTA YP HKBP PEMATANGSIANTAR - Yosua Marasi Parningotan Siagian; Ida Bagus Putu Arnyana; I Gede Margunayasa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the forms of synergy between school policies and parental involvement in supporting the realization of quality education at YP HKBP Private Elementary School in Pematangsiantar. The school is a faith-based educational institution that emphasizes Christian values and Batak cultural heritage in its educational practices. The study employs a descriptive qualitative approach with data collected through semi-structured interviews, participatory observation, and documentation. Research subjects include the school principal, teachers, school committee members, and actively involved parents. The findings reveal that the school's policies, which focus on character development, contextual learning, and parental engagement, have been systematically designed. Parental involvement is not limited to financial support but also includes moral encouragement, participation in school activities, and decision-making through the school committee. This synergy is strengthened by religious values and a strong sense of familial culture within the school community. Identified challenges include parents’ limited literacy and time constraints; however, these are counterbalanced by the school’s open leadership and the HKBP community’s collaborative traditions.